Hubungan Hasil Dipstik Urin (Leukosit Esterase, Nitrit dan Glukosuria) dengan Kejadian ISK pada Pegawai - Tuntun, Maria; Aminah, Siti (Poltekkes Kemenkes Tanjung Karang, 2021)
A urine test with a dipstick is an alternative test for rapid leukocyte and bacterial tests to support the diagnosis of urinary tract infection (UTI). The purpose of this study was to determine the relationship between the results of the dipstick test (leukocyte esterase, nitrite, and glucosuria) with the incidence of UTI. The research is observational analytic with a cross-sectional design, which was conducted in September-October 2020, at Campus